The Legal Implications of Forgery Sale & Purchase Binding Agreement by Notary Public - Samosir, Tetti; Harlina, Indah; Akbar, Fikri Miftakhul (JURNAL AKTA, 2022)
The notary is a public official who is authorized to make authentic deeds, in which the obligation of a notary in carrying out his position must act honestly, reliably, independently, impartially, thoroughly, and safeguard the interests of the parties involved in legal actions. This is known as the precautionary principle for a notary in carrying out his position as a public official. The purpose of this writing is to examine the legal implications of counterfeiting and the responsibility of a notary to the binding sale and purchase agreement he made. The research method used in this paper is normative juridical with a statutory and case study approach. The results and findings obtained after conducting research and analysis of the problems in this paper, namely the legal impact due to the negligence of a notary in making a binding sale and purchase agreement because to forgery, so that the legal consequences of these PPJB are void, this is because it is not in accordance with the legal requirements of an agreement as stated in Article 1320 of the Civil Code, namely those relating to lawful causes. This happens because the notary in carrying out his authority does not carry out his obligations related to the principle of precautionary, therefore the notary must be responsible for his actions that have been carried out in accordance with the law and code of ethics. So it can be concluded that the deed made by the notary is null and void and is not an authentic deed but a private deed.